Phosphorus in dairy farm systems. - Elizondo-Salazar, Jorge Alberto (2005)
Due to the intenseuse of P fertilizers and livestock manure in modern dayagriculture, P has become an accelerator of fresh watereutrophication, resulting in reduced oxygen availabilitybecause of growth of algae and their decomposition. Recentresearch indicates that dietary P management is a key strategyto reduce P imports and accumulation on dairy farms. Thus,a more precise formulation of dairy rations can lead tosubstantial reduction in fecal P excretion without impairinganimal productivity. Some mathematical equations arepresented in order to estimate P excretion by dairy cows.These equations would be very useful when developingnutrient management programs. The objective of the studywas to make a brief commentary of the importance of P in thebody, understand that excess P can be an important threat tosurface waters, and to find the easiest and most economicways to reduce P excretion in dairy farm systems.